Determination of breakage parameters of andesite in dry ball milling - Musa, Jerome S.; Mendoza, Herman D. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
This study aims to determine the breakage parameters of andesite in dry ball milling; namely the specific rate of breakage Si and the breakage distribution function Bij. A prototype batch mill with length of 20 inches and diameter of 20 inches was used. The other parameters used are 8 lifter bars and 30 degree face angles for the lifter bars. Determination of the breakage parameters required a mono size feed grinded at different time intervals. The size intervals and time used are as follows: (i) size intervals: 2000-850 μm, 850-500 μm, 500-300 μm, and 300-180 μm; and, (ii) Grinding time: 0.5,1,3,5, and 10 minutes. The ball mill charge is composed of mono sized one-inch steel ball and 3kg of mono sized feed. The Si and Bij parameters were obtained using the size distribution analysis at different grinding times. A previous grinding model was used in order ot evaluate theoretical weights of a previous grinding study from their starting feed and was compared to the actual result of the said study. The percent deviation ranges from 10%-26% and this difference is attributed to the deviation from linearity of both Si and Bij plots over time on the finer size intervals.
Thesis (M.S. Metallurgical Engineering)--University of the Philippines Diliman
Keywords: Ball mills -- Grinding media; Andesite